Samuel Butler - Holt, Lee E. (Twayne, 1964)
"The acclaimed Twayne's Authors Series of literary criticism offers in-depth introductions to the lives and works of writers, to the history and influence of literary movements and to the development of literary genres. Twayne's Authors Series features the content of nearly 600 books that comprise three print series -- United States Authors, English Authors and World Authors -- each of which were carefully coordinated with input from librarians and educators to include authors universally studied in high schools and colleges. Twayne's Authors Series is devoted to literary critical interpretation and discussion written for readers ranging from high school students to scholars. Each entry explores criticism with new insights and original points of view. Extensive coverage This series spans the literary tradition through hundreds of years and includes 600 authors from around the world -- from Aeschylus to Iris Murdoch. In addition to critical introductions to the lives and works of these authors, Twayne's Authors Series also illuminates the history and influence of literary movements and the development of literary genres. Each treatment devotes 175 to 200 pages to the critical interpretation and discussion of one author's life and works, taking into account important contributions to scholarship and criticism."--Publisher's description.
Keywords: Butler, Samuel <1835-1902> - Etude et critique; Butler, Samuel <1835-1902> -- Criticism and interpretation; Butler, Samuel -- 1835-1902